Sams teach yourself Adobe Flash CS3 Professional in 24 hours - Kerman, Phillip (Sams teach yourself., 2007)
Sams Teach Yourself Adobe Flash CS3 Professional in 24 Hours Phillip Kerman 24 Proven One-hour Lessons In just 24 lessons of one hour or less, you will be able to create dynamic animations using Adobe® Flash® CS3 Professional. Using a straightforward, step-by-step approach, each lesson builds on the previous ones, enabling you to learn the essentials of Flash from the ground up. Step-by-step instructions carefully walk you through the most common Flash tasks. Quizzes and Exercises at the end of each chapter help you test your knowledge. By the Way notes present interesting information related to the discussion. Did You Know? tips offer advice or show you easier ways to do something. Watch Out! cautions alert you to possible problems, and give you advice on how to avoid them. Learn how to ... o Create, optimize, and export dynamic animated movies for the Web, disk, or CD o Integrate Flash animations with static HTML pages o Use Flash's vector graphics tools, including filters and blends, to create drawings and animations o Use digital video in Flash movies o Animate using time-tested techniques and Flash's special "tweening" features o Create powerful, interactive movies using the basics of ActionScript o Design Button, Graphic, and Movie Clip symbols and use them over and over without increasing file size o Import existing graphics from Illustrator® and Photoshop® Phillip Kerman is an internationally recognized expert on the use of the Web and multimedia for training and entertainment. He frequently presents at Flash user conferences and has taught Flash and other authoring tools in workshops around the world. Register your book at www.samspublishing.com/register for convenient access to downloads, updates, and corrections as they become available